THE EFFECT OF GOOD CORPORATE GOVERNANCE MECHANISMS AND COMPANY SIZE ON THE TIMELINESS OF FINANCIAL STATEMENT SUBMISSION IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2021-2023 - Afrilia, Putri; Rahayu, Sri; Erwati, Misni (Universitas Nusa Cendana, 2025)
The study investigates the impact of Good Corporate Governance Mechanisms and company size on the accuracy of financial reporting, employing a quantitative approach. The research focuses on companies in the Property and Real Estate sector listed on the Indonesian Stock Exchange during the 2021-2023 period. A purposive sampling method was used to select 64 companies, resulting in a total of 192 observations over three years. Data analysis was performed using logistic regression with IBM SPSS version 26. The findings indicate that managerial ownership, institutional ownership, and audit committees positively influence the accuracy of financial reporting. However, company size and independent commissioners do not significantly impact the timeliness of financial report submissions. Keywords: Timeliness of Submission of Financial Statements; Audit Committee ; Independent Commissioner ; Managerial Ownership ; Institutional Ownership; Company Size